Gujarātanāṃ Śaikshaṇika pragati tathā vikāsa : Amadāvāda Ejyukeśana Sosāyaṭīnā prayatna - Mavalankar, Ganesh Vasudeo, 1888-1956 (SAMP early 20th-century Indian books project ;, 1951)
On educational development programmes in Gujarat, India.